CHARACTERISTIC OF THE COMPLEX MARKETING COMMUNICATIONS ELEMENTS - Kovalenko, Natalia; Remyha, Yuliia (Proceedings of National Aviation University (archive), 2016)
Purpose: The purpose and objectives of the article are detailed characterization of marketing communication’s elements and characteristics of synthetic and communications. Methods: The stages of the campaign and main advantages and disadvantages of advertising have been disclosed and analyzed in the article. The marketing communication and some elements of marketing communications, the issues of formation and development of the theory of marketing communications have been studied. Results: This article describes the elements of marketing communications factors and basic tools of marketing communications: advertising, personal selling, complex sales promotion, publicity and public relation, direct marketing. Discussion: Companies must also transmit information to customers and carefully carry out selection of such information. For this order is a complex system of marketing communications. Often marketing communications identified with the products promotion which leads to a false understanding of the nature and, consequently, to the irrational use potential of marketing communications in market activity.